Effect of erythropoietin-stimulating agent on uremic inflammation - Tanaka Yuri; Joki Nobuhiko; Hase Hiroki; Iwasaki Masaki; Ikeda Masato; Ando Ryoichi; Shinoda Toshio; Inaguma Daijo; Sakaguchi Toshifumi; Komatsu Yasuhiro; Koiwa Fumihiko; Yamaka Toshihiko; et al. (BMC, 2012)
Abstract Background The goal of the present study was to explore the effect of medications that are commonly prescribed for CKD patients on uremic state. Methods This was a cross-sectional study. From January 2006 to October 2009, 1,623 patients with end-stage kidney disease (ESKD) commenced hemodialysis (HD) at the 9 participating hospitals. The criteria for exclusion from the database were 1) serum C-reactive protein (CRP) > 3 mg/dL, 2) WBC count > 9,000/mm3 or <4,000/mm3, and 3) patients with cancer, immune complex disease, or vasculitis. A total of 900 patients were entered into the final database. We explored the association of serum CRP just before the first HD session with clinical characteristics, laboratory data, and medications for CKD in the predialysis period. Results On univariate analysis, age, CTR, eGFR, and WBC were significantly correlated with CRP. Systolic and diastolic blood pressure, serum albumin, LDL-C, HDL-C, Hb, Cr, and Ca were inversely associated with CRP. Use of erythropoietin-stimulating agents (ESA) using (r = −0.111, p = 0.0015), renin-angiotensin-aldosterone system inhibitors (r = −0.083, p = 0.0154), and calcium channel blockers (r = −0.1, p = 0.0039) was also negatively correlated with CRP. However, only use of ESA showed a significant negative correlation with CRP that was independent of other clinical factors and CKD medications on multiple regression analysis. Conclusion ESA may strongly reduce uremic inflammation in addition to improving anemia. To confirm this potential effect, a large-scale longitudinal study would be required.